Flowers Bakery Enterprise / Nur Ain Abd Halim... [et al.] - Abd Halim, Nur Ain; Shaharudin, Nur Afizah; Jamal, Norfaeza; Ghazali, Nur Aqilah; Rosli, Nur Najihah; Wan Abd Rahman, Wan Norsyahirah (2019)
We are the company that making cakes and brownies with fluffy and affordable price around Seremban. We are choosing to make this product because of our vision was to establish good quality and halal of food product that produced by Bumiputera in the global industry of pastry food product quality in the world. We also provide many benefit for the people that have big event such as birthday party, anniversary because with the low price but they can get customade cake and also free delivery service. We put an average price which are RM 15 for the cake and RM35 for our brownies because we want people that come from different age could buy our product and become happy to taste our product. We believe that our product can reach people heart and able to compete with other competitor in the pastry industry. The business will start on 2020 which is one year from now. As we already decide thar we need eight person which is ourselves to fill the following position in our company. For example, general manager, financial manager, marketing manager and operation managers and two staffs. We believe that we could handle the things since we have different ability and also known each other very well. The place also at the strategic place that able for our business to expand. It is because the area around Seremban help us to get large target size because of the population which are come from workers ,university students, primary and secondary student .